2008
DOI: 10.1080/10934520802330206
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate characterization of elements accumulated in King BoleteBoletus edulismushroom at lowland and high mountain regions

Abstract: Based on ICP-MS, ICP-OES, HG-AAS, CV-AAS and elementary instrumental analysis of King Bolete collected from four sites of different soil bedrock geochemistry considered could be as mushroom abundant in certain elements. King's Bolete fruiting bodies are very rich in K (> 20 mg/g dry weight), rich in Ca, Mg, Na, Rb and Zn (> 100 microg/g dw), and relatively also rich in Ag, Cd, Cs, Cu, Fe, Mn and Se (> 10 microg/g dw). The caps of King Bolete when compared to stipes around two-to three-fold more abundant are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 30 publications
8
65
3
1
Order By: Relevance
“…Earlier studies reported that M. procera has the ability to efficiently bioconcentrate Hg [54][55][56][57]. This species, apart from being rich in the essential elements (including Cu and Zn), is also rich in Cd, Pb, Hg, and Ag [2,14,26,40,56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies reported that M. procera has the ability to efficiently bioconcentrate Hg [54][55][56][57]. This species, apart from being rich in the essential elements (including Cu and Zn), is also rich in Cd, Pb, Hg, and Ag [2,14,26,40,56].…”
Section: Resultsmentioning
confidence: 99%
“…• Boletus spp., or the bay bolete (Imleria badia) • Yellow-cracked bolete (Boletus subtomentosus) and golden bolete (Xerocomellus chrysenteron); Boletus spp., and in majority the king bolete (Boletus edulis) • Common chanterelle (Cantharellus cibarius) [10] Mushrooms, especially wild grown mushrooms and the edible species in particular, have been reported to be rich in mineral constituents as well as in some toxic metals [11][12][13][14][15][16]. As such, mushroom studies have shown that some mushroom species are rich sources of essential trace elements.…”
mentioning
confidence: 99%
“…In accordance of literature data concentration of cadmium in fruit bodies on unpolluted areas vary between 0,5 to 5 µg/g DM, it depends on the species of fungi. The highest cadmium level was determined in B. edulis (point 7 of zone I) and was 8,8 µg/g, but it is normal values for this species (Ouzouni et al, 2009;Durali et al, 2005;Popova, 2011, Kalač et al, 2000Kalač, 2010;Rudawska et al, 2005;Falandysz et al, 2008;Malinowskaa et al, 2004). Thus B. edulis can be considered as moderate cadmium accumulators.…”
Section: Discussionmentioning
confidence: 99%
“…From the data for numerous species, usual chromium contents were determined as 0,5 and 5 µg/g DM (Ouzouni et al, 2009;Durali et al, 2005;Kalač et al, 2000, Kalač, 2010Ivanov et al, 2008;Rudawska et al, 2005;Falandysz et al, 2008;Malinowskaa et al, 2004;Svoboda et al, 2007). Probably P.ostreatus and R. invalli is accumulator of chromium.…”
Section: Discussionmentioning
confidence: 99%
“…El estudio de las interacciones entre metales pesados y hongos estaḿ otivado, entre otras cosas, por la ubicuidad y presencia de los hongos en ha´bitat contaminados, asıć omo por la captacio´n y traslocacio´n de metales pesados a los carpo´foros (setas) de macromicetos comestibles, por sus repercusiones sanitarias y ecotoxicolo´gicas, incluso por sus posibles aplicaciones biotecnolo´gicas derivadas de la capacidad de algunos hongos para captar y fijar metales (Quinche, 1987;Gadd, 1993;Melgar, Alonso, Pe´rez-Lo´pez, & Garcı´a, 1998;Alonso, Salgado, Garcı´a, & Melgar, 2000;Zaichick, 2002;Alonso, Garcı´a, Pe´rez-Lo´pez, & Melgar, 2003, 2004Jonnalagadda, Pienaar, & Haripersad, 2006;Yamac, Yildiz, Sarikurkcu, Celikkollu, & Solak, 2007;Falandysz et al, 2008aFalandysz et al, , 2008b.…”
Section: Introduccio´nunclassified